2022
DOI: 10.1186/s12939-022-01621-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex work community participation in criminalized environments: a community-based cohort study of occupational health impacts in Vancouver, Canada: 2010–2019

Abstract: Background Sex work criminalization and occupational stigma pose barriers to sex workers’ access to support services, including community participation — engagement with sex work specific community organizing at both formalized and grassroots capacities. In light of gaps in evidence regarding impacts of community participation on sex workers’ occupational health in higher-income settings, we evaluated engagement in community participation and associations with occupational sexual health outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Research has shown that im/migrant sex workers often fear that accessing sexual health services or disclosing their work to healthcare providers could result in negative impacts on their workplace (e.g., police raids) or ability to work [ 55 , 57 , 56 , 60 ]. Finally, recent research suggests im/migrant workers are less likely to engage in sex worker community organizing and sex work-specific services [ 24 ], which have been linked to improved sexual health outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that im/migrant sex workers often fear that accessing sexual health services or disclosing their work to healthcare providers could result in negative impacts on their workplace (e.g., police raids) or ability to work [ 55 , 57 , 56 , 60 ]. Finally, recent research suggests im/migrant workers are less likely to engage in sex worker community organizing and sex work-specific services [ 24 ], which have been linked to improved sexual health outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous AESHA research [ 24 ], this analysis sought to measure prevalence and correlates of HIV/STI testing at enrollment. The outcome for this analysis was a binary (Yes/No) variable measuring if a participant had received HIV or STI testing within the six months prior to their baseline visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though facing ongoing inequities, policing and gentrification, organizers within the DTES have been successful in scaling up low-barrier supports, including harm reduction and safe supply services during the ongoing overdose pandemic, as well as sex work-specific services. Community level factors, such as utilization of and engagement with such services have been previously shown to support sex workers' occupational health, safety, and wellbeing (Pearson et al 2022). Throughout the COVID-19 pandemic as well, sex work organizations have been highly successful in pivoting their services in order to reach diverse communities of sex workers, despite lockdowns and service interruptions (Benoit and Unsworth 2022;Lam 2020b;PACE Society 2020;St.…”
Section: Discussionmentioning
confidence: 99%
“…Further, community empowerment-based approaches have been linked to increased sex worker collectivisation, solidarity and condom use, and reduced HIV and STI transmission, highlighting both the community-level and broader public health impacts of the services provided by sex work community organisations. 17 18 However, many such organisations were forced to close doors and/or scale back services during pandemic lockdowns. While community groups globally swiftly set up emergency hardship funds and informal forms of mutual aid to their members during COVID-19—demonstrating solidarity and resilience amid the public health crisis 5 6 9 10 13 19–21 —limited empirical research has examined the impacts of interrupted access to sex worker-specific community services among sex workers during COVID-19.…”
Section: Introductionmentioning
confidence: 99%